Equipotent Dose and Cost Comparison of Atracurium and Rocuronium in Laboratory Pigs Anesthetized with Propofol - Eleonora Benetti; Alessandro Mirra; Olivier Louis Levionnois (Animals)
Neuromuscular blocking agents such as atracurium and rocuronium are commonly used during anesthetic procedures in laboratory pigs. However, species-specific dosing guidelines remain limited, leading to reliance on data extrapolated from other species. This prospective, blinded study aimed to determine the equipotent dose for atracurium (A) and rocuronium (R) in laboratory pigs receiving propofol and to compare their cost-effectiveness. Twelve healthy animals were randomly distributed according to the drug administered (n = 6 per group). For both drugs, the infusion rate was adjusted following an up-and-down titration to maintain a train-of-four count between 3 and 4. Group differences were analyzed using the Wilcoxon signed-rank test. The bolus induction dose (mg/kg) was comparable between atracurium (2.3 [1.8–2.6]) and rocuronium (2 [2]), while atracurium was associated with higher costs (CHF/kg: A, 1.122 [0.878–1.366] versus R, 0.208 [0.208–0.208]; p = 0.002725). The maintenance infusion rate (mg/kg/h) was approximately 40% lower for atracurium (2.7 [2.5–2.8]) than for rocuronium (4.5 [4.4–4.5]; p = 0.004922), yet the maintenance cost (CFH/kg/h) remained higher for atracurium (A: 1.30 [1.22–1.37] versus R: 0.47 [0.45–0.47]; p = 0.0043). This study reports higher doses for anesthetized pigs compared to other species and demonstrates that rocuronium offers superior cost-effectiveness compared to atracurium under these experimental conditions.